2019
DOI: 10.1212/wnl.0000000000007716
|View full text |Cite
|
Sign up to set email alerts
|

Progression of cognitive decline before and after incident stroke

Abstract: ObjectiveTo determine the trajectory of cognitive decline before and after incident stroke.MethodsBy using data from the English Longitudinal Study of Ageing, we studied 9,278 participants without dementia with no history of stroke who underwent cognitive assessment at baseline (wave 1) and at least 1 other time point (waves 2–7). We used linear mixed models to analyze repeated measures and longitudinal data.ResultsAmong the 9,278 participants (56.8% women, mean age 63.1 ± 10.3 years), 471 (5.1%) incident stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
95
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(100 citation statements)
references
References 35 publications
3
95
1
1
Order By: Relevance
“…### LR χ 2 ( 8 ), Likelihood Ratio test model 1 vs. model 2 with 8 degrees of freedom; hypothesis test of whether there is an effect of stroke subtype. ***LR χ 2 ( 5 ), Likelihood Ratio test model 2 vs. model 3 with 5 degrees of freedom; hypothesis test of whether there is an effect of time for at least one stroke subtype. ‡ p < 0.01.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…### LR χ 2 ( 8 ), Likelihood Ratio test model 1 vs. model 2 with 8 degrees of freedom; hypothesis test of whether there is an effect of stroke subtype. ***LR χ 2 ( 5 ), Likelihood Ratio test model 2 vs. model 3 with 5 degrees of freedom; hypothesis test of whether there is an effect of time for at least one stroke subtype. ‡ p < 0.01.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have reported conflicting results regarding the prognosis for patients suffering PSCI; these have indicated deterioration, no progression, and even improvement in cognition over time for subgroups (4)(5)(6)(7)(8)(9)(10)(11). Several cognitive domains are affected in PSCI; of these, impairment in attention and executive function seem to be the most prevalent and severe shortly after and a long time after suffering a stroke (12)(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the increasingly recognized poststroke cognitive impairment (PSCI), which is increasingly recognized as associated with ischemic stroke (3), the incidence of cognitive dysfunction and the risk factors associated with the cognitive trajectory after ICH onset remain mostly unknown. This is likely due to the lower incidence of ICH and the high mortality rate observed during the acute stage (4)(5)(6). Indeed, ICH survivors are at high risk of cognitive decline following stroke onset, consequently affecting quality of life, and posing an increased social and economic burden.…”
Section: Introductionmentioning
confidence: 99%
“…Cognitive impairment can develop acutely in the immediate aftermath of stroke with some degree of recovery expected over time. However, there is also a risk of a more chronic neurodegeneration as some, but not all, individuals can experience gradual and protracted cognitive decline in the years following stroke at a greater rate than would be expected from aging alone [6,7]. Consequently, there is an increasing incidence of dementia in the years following stroke [41].…”
Section: Discussionmentioning
confidence: 99%
“…Despite this initial recovery, cognitive impairment occurs at a high frequency, persisting well past the subacute recovery period [2,3]. Stroke places some individuals at risk of an increased rate of cognitive decline, even several years after stroke, and a history of stroke approximately doubles the long-term risk of incident dementia [2,[4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%